2012
DOI: 10.5194/isprsarchives-xxxviii-1-c22-75-2011
|View full text |Cite
|
Sign up to set email alerts
|

Context-Based Urban Terrain Reconstruction From Uav-Videos for Geoinformation Applications

Abstract: ABSTRACT:Urban terrain reconstruction has many applications in areas of civil engineering, urban planning, surveillance and defense research. Therefore the needs of covering ad-hoc demand and performing a close-range urban terrain reconstruction with miniaturized and relatively inexpensive sensor platforms are constantly growing. Using (miniaturized) unmanned aerial vehicles, (M)UAVs, represents one of the most attractive alternatives to conventional large-scale aerial imagery. We cover in this paper a four-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…After image matching and the generation of a digital terrain model (DTM), a rule-based classification of buildings and vegetation is carried out, and the boundary polygons of the buildings are extracted. Optionally, the polygons can be regularised (Bulatov et al, 2011).…”
Section: Bulatov Fraunhofer Institute Ettlingen Germany (Fie)mentioning
confidence: 99%
See 1 more Smart Citation
“…After image matching and the generation of a digital terrain model (DTM), a rule-based classification of buildings and vegetation is carried out, and the boundary polygons of the buildings are extracted. Optionally, the polygons can be regularised (Bulatov et al, 2011).…”
Section: Bulatov Fraunhofer Institute Ettlingen Germany (Fie)mentioning
confidence: 99%
“…Section 3.1) a detailed roof analysis is performed, using a RANSAC based approach for the initial clustering of normal vectors (Bulatov et al, 2011).…”
Section: Bulatov Fraunhofer Institute Ettlingen Germany (Fie)mentioning
confidence: 99%
“…Therefore, this study investigates the effect of number International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, Volume XL-2/W2, ISPRS 8th 3DGeoInfo Conference & WG II/2 Workshop, 27 -29 November 2013, Istanbul, Turkey GCPs in image processing based on block configuration. A proposed image registration introduced by (Bulatov et al, 2011) was used in this study; co-registration process and georeferencing process in DO.…”
Section: Introductionmentioning
confidence: 99%
“…Bulatov et al (2012) used an imagebased DSM to compute normal vectors for each pixel, while Omidalizarandi and Saadatseresgt (2013) performed region growing on image based point clouds to form planar segments. However, it was found that errors from planar segmentation can arise at the location of the planar boundaries (Omidalizarandi and Saadatseresgt, 2013).…”
Section: Related Workmentioning
confidence: 99%